PENGARUH KESADARAN MERK, PERSEPSI KUALITAS, DAN LOYALITAS MERK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE VIVO PADA ANGKASA CELL DI KABUPATEN BLORA - Fahlefi, Diva RIza; Indriastuti, Ariyani (JURNAL STIE SEMARANG, 2019)
The increasing level of competition for companies has resulted in companies competing to win consumers. The purpose of this study was to analyze the effect of brand awareness, perceived quality and brand loyalty on Mobile Vivo Purchase Decisions in Angkasa Cell Store in Blora Regency. The population in this study is all customers or consumers who used or made mobile phone purchasing decisions in Angkasa Cell Store in Blora Regency which amounts to 154 customers.  The sampling technique used was purposive sampling to obtain 63 respondents. The method of data analysis uses multiple linear regression. The results of the study show that the brand awareness variable obtains a tcount of 3.958> ttable 1.66) with a significance of 0,000 means brand awareness has a positive and significant influence on purchasing decisions. The perceived quality variable with a tcount (3.694)> t table (1.66) with a significance of 0,000 means that the perception of quality has a positive and significant influence on purchasing decisions. Brand loyalty variable with a value of tcount (3,438)> t table (1.66) with a significance of 0.001, means that brand loyalty has a positive and significant influence on purchasing decisions. In order for the consumer confidence of Vivo mobile phone in Angkasa Cell Store in Kabupaten Blora can be stronger and increase purchasing power, it is recommended to increase brand awareness through promotion.